Microbiota and antibiotic exposure in sarcoidosis - Ucciferri, Claudio; Moffa, Livia; Tana, Claudio (Frontiers in Immunology, 2025)
BackgroundSarcoidosis is a multisystem granulomatous disorder characterized by excessive immune activation in genetically predisposed individuals. Despite decades of investigation, its etiology remains unresolved. Emerging evidence indicates that disruptions in host–microbiota homeostasis may contribute to immune dysregulation and disease persistence, challenging the traditional view of sarcoidosis as a purely immune-mediated condition.PerspectiveRecent findings have revealed alterations in both respiratory and intestinal microbiota among patients with sarcoidosis, suggesting that microbial dysbiosis may influence T-cell polarization and granulomatous inflammation. Antibiotic exposure, particularly to macrolides and tetracyclines, represents a largely overlooked modifier that may alter this equilibrium through combined microbiota-dependent and immunomodulatory mechanisms. Given the frequent use of antibiotics in these patients for respiratory infections or off-label anti-inflammatory purposes, understanding their effect on microbial diversity, immune signaling, and disease course warrants systematic evaluation.Translational OutlookWe propose an integrative framework combining microbiota profiling, immune phenotyping, and therapeutic exposure to delineate microbiota–immunity interactions in sarcoidosis. Multi-omics strategies, supported by advanced computational and network-based analyses, could uncover microbe–immune signatures predictive of chronicity or treatment response. Defining how antibiotics shape these interactions may provide a foundation for microbiota-informed, immune-targeted, and ultimately personalized interventions.ConclusionDeciphering the interplay between microbiota composition, antibiotic exposure, and immune regulation has the potential to reshape our understanding of sarcoidosis pathogenesis and to guide the development of precision-based therapeutic strategies.